Chinese non-psychiatric hospital doctors’ attitudes toward management of psychological/psychiatric problems - Wang, Jun (BMC Health Serv Res, 2017)
BACKGROUND: Psychiatric comorbidities are common among patients treated for physical disorders. Attitudes of non-psychiatric doctors toward psychological/psychiatric problems have significant implications for care provision in the general hospital setting. Our objective was to investigate non-psychiatric doctors’ attitudes in China. METHOD: An anonymous online questionnaire pertaining to relevant attitudes was distributed to Chinese hospital-based non-psychiatric doctors using a mobile App. RESULTS: A total of 306 non-psychiatric doctors in China voluntarily completed the questionnaire. All but two (99.3%) respondents agreed with the importance of psychological factors underlying physical illness and 85.6% agreed they had a high degree of responsibility for management of patients’ emotional problems. Most respondents endorsed routine assessment of patients’ psychological factors and were willing to consider psychiatric referrals for patients in need; despite 52.0% believing that mental health care by general hospital doctors was impractical. Almost all respondents welcomed more contact with psychiatric services and indicated a need for more time and professional help to manage psychological issues. Respondents’ demographic characteristics and vocational status had some influence on attitudes; female doctors were more likely and surgeons less likely to consider psychological assessment and emotional care for patients with physical illness. More doctors working in hospitals with established consultation-liaison psychiatric services did not feel responsible for their patients’ emotional care (17.7% vs. 6.6%, P = 0.012). CONCLUSIONS: Our pilot survey demonstrates a potential generally positive attitude toward management of patients’ psychological problems and an urgent need for more time and specialist support for non-psychiatric doctors in China.